(untitled) (Statistics, Optimization & Information Computing, 2021)
This article aims to present and analyse a modified two-parameter version of the Half-Logistic lifetime model. The hazard function, quantile function, asymptotic, linear combination, extreme value, moments, incomplete moments, residual entropies, moment generating function and order statistics, all theoretical properties of this model that are derived and discussed in depth. By performing a simulation analysis, the various techniques of estimation are compared to the estimates of the maximum likelihood of parameters.Finally, two actual data sets have been applied to illustrate the goals of this article.